Keterampilan Berbicara sebagai Sarana Pengembangan Bahasa Siswa Sekolah Dasar - Nabila Asmaul Husna; Atikah Salsabillah; Yelsi Melinda Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the role of speaking skills in supporting language development among elementary school students through a Narrative Literature Review (NLR) approach. This method is employed to examine and synthesize various relevant sources, including books, scholarly journal articles, and previous research findings. The data were analyzed descriptively by identifying key themes, patterns, and relationships among concepts related to speaking skills and students’ language development. The findings indicate that speaking skills play a significant role in enhancing students’ language abilities, particularly in terms of vocabulary mastery, sentence structure, and communication fluency. These skills are influenced by several factors, including linguistic, psychological, environmental, and pedagogical aspects. In addition, the implementation of interactive and student-centered learning strategies, such as group discussions, role-playing, question-and-answer sessions, and presentations, has been proven effective in improving students’ speaking abilities. However, several challenges remain, including low self-confidence and limited opportunities for students to practice speaking. Therefore, collaborative efforts among teachers, schools, and families are needed to create a supportive learning environment. In conclusion, speaking skills should be developed systematically and continuously to support students’ overall learning success.